2019
DOI: 10.1038/s41586-019-1430-x
|View full text |Cite
|
Sign up to set email alerts
|

A mutation-independent approach for muscular dystrophy via upregulation of a modifier gene

Abstract: doi: bioRxiv preprint Collectively, our data demonstrate the feasibility and therapeutic benefit of CRISPR/dCas9-mediated modulation of a disease modifier gene, which opens up an entirely new and mutation-independent treatment approach for all MDC1A patients. Moreover, this treatment strategy provides evidence that muscle fibrosis can be reversible to some degree, thus extending the therapeutic window for this disorder. Our data provide a proof-of-concept strategy that can be applied to a variety of disease mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 37 publications
1
85
0
1
Order By: Relevance
“…For example, overexpression of a functional endogenous copy has the potential to rescue human diseases caused by haploinsufficiency [19]. Alternatively, overexpression of a protein similar to one encoded by a mutant gene could treat human diseases caused by recessive mutations [20]. For example, congenital muscular dystrophy type 1A (MDC1A) is an autosomal recessive disorder caused by mutations in LAMA2 that cause production of nonfunctional laminin-α2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, overexpression of a functional endogenous copy has the potential to rescue human diseases caused by haploinsufficiency [19]. Alternatively, overexpression of a protein similar to one encoded by a mutant gene could treat human diseases caused by recessive mutations [20]. For example, congenital muscular dystrophy type 1A (MDC1A) is an autosomal recessive disorder caused by mutations in LAMA2 that cause production of nonfunctional laminin-α2.…”
Section: Discussionmentioning
confidence: 99%
“…For example, congenital muscular dystrophy type 1A (MDC1A) is an autosomal recessive disorder caused by mutations in LAMA2 that cause production of nonfunctional laminin-α2. Viral overexpression of Lama1, which encodes a similar protein, in a mouse model of MDC1A improved disease symptoms and slowed progression [20]. Thus, the development of a system that yields robust activation and yet is small enough to be cloned into a virus vector, is an important priority for therapeutic applications.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, strategies such as AAV-mediated expression of mini-Agrin (Moll et al, 2001), CRISPR/CAS9-mediated over expression of laminin-alpha1 (Kemaladewi et al, 2019), or treatment with recombinant laminin-111 (Rooney et al, 2012) would be logical choices to compensate for the missing laminin-alpha2. LAMA1 is similar to LAMA2, thus overexpression would compensate for lack of LAMA2 function while minimizing the risk of an immune response to laminin-111.…”
Section: Therapeutic Strategies Targeting Fibrosismentioning
confidence: 99%
“…It was reported several years ago that transgenic expression of the laminin α1 subunit in dy 3K /dy 3K mice substantially rescued both the muscle and peripheral nerve phenotypes (Gawlik et al, 2004(Gawlik et al, , 2006. Furthermore, in a recent study, it was shown that activation of expression of the α1 subunit by CRISPR-dCas9-mediated upregulation of Lama1 improved the dystrophic phenotype of the dy 2J /dy 2J mouse (Kemaladewi et al, 2019). This represents a new approach to the treatment of LAMA2-MD.…”
Section: Linker Proteins and Repair Of Dystrophic Basement Membranesmentioning
confidence: 83%